Gambaran Asuhan Keperawatan Luka Phlebitis pada An. R dan An. M dengan Pemasangan Infus di RSUD Haji Makassar - Saputri, Aulia; Lusiana, Evi; Nofianti, Nofianti; Mikawati, Mikawati (Jurnal Persada Husada Indonesia, 2024)
Phlebitis is venous inflammation caused by chemical, mechanical or bacterial irritation which is often caused by complications from intravenous therapy. To find out the description of the management of phlebitis wounds in children with infusion at Haji Hospital Makassar. The research method in preparing this case study is descriptive and action observation. The management of phlebitis wounds carried out by nurses was by giving warm compresses, where subject 1 was given for 2 days while subject 2 was given for 3 days according to the SOP at the hospital. Evaluation of the management of phlebitis wounds carried out by nurses by giving warm compresses to patient subject 1 whose phlebitis wound resolved on day 2 while in patient subject 2 the phlebitis wound resolved on day 3. From the results of research conducted by the author in the Al-Kautsar Room, Haji Hospital Makassar on 10-13 June 2024, the results showed a description of the actions for treating phlebitis wounds in accordance with the SOP. In dealing with phlebitis wounds, good and appropriate care has been taken. When providing treatment for phlebitis wounds, you should take action by the established SOP procedures.